To what extent the weight changes impact the risk of hypertension among menopausal women: insights from Tehran lipid and glucose study - Marzieh Saei Ghare Naz; Maryam Mousavi; Mahsa Noroozzadeh; Maryam Farahmand; Fereidoun Azizi; Fahimeh Ramezani Tehrani (BMC, 2024)
Abstract Background & aim The association between weight change and incident hypertension (HTN) in menopausal women has not been well characterized. This study aimed to determine whether weight changes after menopausal years make a difference in incidents of hypertension. Materials & methods This population-based study was performed using data collected from Tehran Lipid and Glucose Study cohort (1999-2018). Women who had natural and early menopause were followed up every 3 years. Data gathering was performed through the standard protocol of the study. Statistical analysis was performed using multivariable Cox hazard regression analysis. We used the 'survival' package in the R software version 3.6.0 to fit survival models. Results A total of 487 menopausal women met the inclusion criteria; 62.6% had natural menopause and remained had early menopause. Among the participants, 65.5% experienced HTN. The highest proportion of participants had > 5% weight gain, while the lowest had 3-5% weight gain. Either losing body weight (lost > 5%: HR: 0.44; CI 95%, 0.32, 0.62; p < 0.001), (lost 3-5%; HR: 0.47; CI 95%, 0.26, 0.84; p = 0.01), and weight gain > 5% (HR: 0.69; CI 95%, 0.51, 0.91; p = 0.01), were associated with decreased risk of HTN after adjustment for confounders. In this study, weight loss and gain have a protective impact on the development of HTN in subjects. For incident HTN, age (HR: 1.04 (1.01, 1.08), p = 0.004), fasting blood glucose (HR: 1.01, CI 95%:1.00, 1.01; p < 0.001), body mass index (1.02 (1.00, 1.05), p = 0.03) and smoking (1.70 (1.11, 2.58), p = 0.01) were positively associated with HTN. Conclusions Our study indicates the significant association of weight change with hypertension risk in later life among menopausal women.